An assessment on the promotional strategies of the Philippine Animal Welfare Society on its animal adoption program towards the residents of the City of Manila: basis for a promotional campaign - Altar, Shaira Del C.; Pebres, Mary Joy Maynald B.; Reyes, Arvin Kyle M.; Rosales, Eilleen Claire A. and Samson, Louise B. 4 0 16; 5
u
Thesis: (Bachelor in Mass Communication) - Pamantasan ng Lungsod ng Maynila ,2018.
Keywords: 2 -- 0; 6; 20; 20; 2